The torture doctors : human rights crimes & the road to justice - Miles, Steven H. 2020- (Georgetown University Press, 2020)
Steven H. Miles reveals a horrifying, global, yet hidden medical specialty: the torture doctor. Physicians are essential to the modern practice of torture. Their countries employ them to invent techniques to break people down without leaving scars. They falsify death certificates to say that a murdered prisoner died of natural causes, They monitor prisoners being tortured to keep them alive for the next day of pain. Torture doctors work for dictatorships and even democracies such as the United States, United Kingdom, and Spain. Doctors torture with impunity in most cases. With rare exceptions, governments protect them and medical associations and licensing boards leave them alone. This book examines who they are, what they do, and how they escape accountability. It also traces the beginnings of a movement to bring them to justice and recommends ways that the international human rights community can hold these perpetrators accountable. Finally, it shows how physicians can be brought back to their proper role of promoting health and human rights. This is a shocking and and little known story that must be revealed